What factors influence parents' perception of the quality of life of children and adolescents with neurocardiogenic syncope?. Issue 1 (December 2016) - Grimaldi Capitello, Teresa; Fiorilli, Caterina; Placidi, Silvia; Vallone, Roberta; Drago, Fabrizio; Gentile, Simonetta
Abstract Background Health-related quality of life, which can be investigated using self-reports or parental reports, could help healthcare providers understand the subjective perception of well-being of children suffering from recurrent syncopal episodes. Quality of life is not only a measure of health but is also a reflection of patients' and parents' perceptions and expectations of health. This study assessed: 1) the consistency and agreement between pediatric patients' self-reports and parents' proxy-reports of their child's quality of life; 2) whether this patient-parent agreement is dependent on additional demographic and clinical or distress factors; 3) whether the parents' psychological distress influences children's and parents' responses to questionnaires on quality of life. Methods One hundred and twenty-five Italian children aged 6-18 years old (Mean age 12.75, SD 2.73, 48 % female) and their parents completed the Pediatric Quality of Life inventory with self-reports and parent-proxy reports, the Parenting Stress Index - Short Form questionnaire and the Child Behavior Checklist for ages 6-18. Patients' and parents' scores on quality of life were analyzed via an intra-class correlation coefficient, Spearman's correlation coefficient, Wilcoxon signed-rank test, and Bland-Altman plot. Results Child-rated quality of life was lower than parent-rated quality of life. However, there were no statistically significant differences between pediatric patients' self-reports and their parents' proxy-reports of on quality of life. Clinically significant patient-parent variation in pediatric health-related quality of life was observed. Differences in patient-parent proxy Pediatric Quality of Life inventory Total Scale Score scores were significantly associated with patient age. Conclusion Concerning parents' proxy-ratings of their children's quality of life on the Pediatric Quality of Life inventory, parental stress was found to be negatively associated with their perceptions of their child's psychological quality of life. Indeed, childhood illness is a source of stress for the whole family, and exposes family members to a greater risk of developing psychosocial difficulties. In conclusion, this study invites reflection on the use of cross-informants in investigating the quality of life of young patients with neurocardiogenic syncope and the psychological factors that influence how quality of life is perceived.